Low-Frequency Admittance of Capacitor with Working Substance “Insulator–Partially Disordered Semiconductor– Insulator” - N. A. Poklonski; I. I. Anikeev; S. A. Vyrko (Приборы и методы измерений)
The study of the electrophysical characteristics of crystalline semiconductors with structural defects is of practical interest in the development of radiation-resistant varactors. The capacitance-voltage characteristics of a disordered semiconductor can be used to determine the concentration of point defects in its crystal matrix. The purpose of this work is to calculate the low-frequency admittance of a capacitor with the working substance “insulator–crystalline semiconductor with point t-defects in charge states (−1), (0) and (+1)–insulator”. A layer of a partially disordered semiconductor with a thickness of 150 μm is separated from the metal plates of the capacitor by insulating layers of polyimide with a thickness of 3 μm. The partially disordered semiconductor of the working substance of the capacitor can be, for example, a highly defective crystalline silicon containing point t-defects randomly (Poissonian) distributed over the crystal in charge states (−1), (0), and (+1), between which single electrons migrate in a hopping manner. It is assumed that the electron hops occur only from t-defects in the charge state (−1) to t-defects in the charge state (0) and from t-defects in the charge state (0) to t-defects in the charge state (+1).In this work, for the first time, the averaging of the hopping diffusion coefficients over all probable electron hopping lengths via t-defects in the charge states (−1), (0) and (0), (+1) in the covalent crystal matrix was carried out. For such an element, the low-frequency admittance and phase shift angle between current and voltage as the functions on the voltage applied to the capacitor electrodes were calculated at the t-defect concentration of 3∙1019 cm−3 for temperatures of 250, 300, and 350 K and at temperature of 300 K for the t-defect concentrations of 1∙1019, 3∙1019, and 1∙1020 cm−3.